Effect of high‐temperature AlN buffer on anisotropy of semi‐polar (11‐22) GaN with two pressure growth stages. (14th August 2019) - Han, Jun; Shi, Fengfeng; Xing, Yanhui; Wan, Peiyuan; Gao, Zhiyuan; Hu, Xiaoling; Li, Tao; Cao, Shiwei; Zhang, Yao
Abstract : The low‐temperature GaN (LT‐GaN) and high‐temperature AlN (HT‐AlN) buffer layers were grown on m ‐plane sapphire by metal–organic chemical vapour deposition. The following semi‐polar (11‐22) GaN thin films were deposited under high‐ and low‐pressure growth stages. Anisotropy of (11‐22) GaN grown on HT‐AlN buffer along two in‐planar directions ([11‐2‐3] and [‐1100]) were clearly suppressed, the maximum variation of the X‐ray rocking curve full width at half maximum of (11‐22) GaN on LT‐GaN buffer was 0.2498°, that of (11‐22) GaN on HT‐AlN buffer was 0.0488°. The X‐ray diffraction results of on‐axis and off‐axis both indicated that the crystal quality of the epitaxial GaN layer with HT‐AlN buffer was obviously improved, and surface morphology was much smoother.